Assistance in the Preparation of Financial Statements of the National Zakat Amil Agency (BAZNAS) of the City of Madiun - Kudhori, Ahmad; Kirowati, Dewi; Anggraeny, Shinta Noor (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
This partnership or community service activity aims to provide assistance to leaders, as planners and organizational policy makers, as well as to daily implementers in Baznas Madiun City as executors of operational activities, so that later it is expected that the management is able to conduct internal supervision and daily implementers able to prepare financial reports accordingly PSAK 109 concerning Accounting for Zakat and Infaq / Alms. The steps or methods of activities carried out in this mentoring are: first, conducting class/face-to-face activities by providing accounting material in accordance with PSAK 109. Second, reviewing the financial statements that have been made so far. Third, carry out follow-up by working on financial statements based on PSAK 109. Fourth, provide assistance in preparing financial statements.